Analisis Kontribusi Crowdfunding Syariah Dalam Pengembangan UMKM di Sumatera Utara - Hutabarat, M. Rafiq Efrianda; LathiefIlhamy Nst, M.; Harahap, Muhammad Ikhsan (Jayapangus Press, 2025)
The public’s lack of understanding about the concept of sharia crowdfunding and regulations that do not fully support it are the main obstacles in developing this platform. Support from the government and related institutions in the form of clear regulations and education to the public is very important to maximize the potential of sharia crowdfunding. The aim of this research is to look at the analysis of the contribution of Sharia crowdfunding in the development of MSMEs in North Sumatra. In this research, a descriptive qualitative analysis method was used. The results of this research show that one form of fintech development is the emergence of crowdfunding originating from the internet network. Crowdfunding is a model for individuals, organizations and companies that collect funds from many communities to fund a particular product or project. Sharia crowdfunding is an innovation in the field of financial technology that offers an alternative solution for MSME players to obtain funding through sharia share and sukuk issuance schemes.Sharia SCF also has the potential to be an alternative investment that is easy to carry out and provides adequate protection for investors. Sharia crowdfunding has great potential in developing MSMEs in Indonesia, especially in providing access to financing that is more inclusive and in accordance with sharia principles. With sharia crowdfunding, MSMEs can obtain business capital without having to depend on interest-bearing loans which are often burdensome. Funds obtained from sharia crowdfunding can be used to develop new products or improve existing products, thereby increasing the competitiveness of MSMEs. MSMEs can invest the funds they receive to improve the quality of products and services, which can have an impact on increasing sales and customer loyalty. Sharia crowdfunding allows the wider community to participate in supporting MSMEs, which indirectly empowers communities and strengthens the local economy.